Relationship between Big-5 Personality Traits & Employee Motivation to Transfer: A Study of the Education Sector - Khalid , Shahzad Ahmed; Sarwar, Shakeel (Pakistan Journal of Humanities and Social Sciences, 2023)
The objective of this research is to analyze how the Big Five Personality Traits impact an employee's motivation to transfer training in the education sector. The research aims to determine if specific personality traits such as conscientiousness and openness are more strongly linked to increased motivation to transfer training knowledge into the workplace. A descriptive cross-sectional research design is utilized to examine the findings. The results demonstrate that the Big Five Personality Traits significantly influence training transfer, with openness, conscientiousness, and adaptability having particularly positive effects on motivation to transfer. Consequently, these traits are likely to enhance the probability of successful training transfer.